PENGARUH AUDIT INTERNAL DAN KINERJA KARYAWAN TERHADAP PENGENDALIAN INTERNAL SERTA DAMPAKNYA TERHADAP PENCEGAHAN KECURANGAN DI PT. COMMIT TRANS ANGKASA DENGAN MENGGUNAKAN METODE ANALISIS JALUR - Kenny Cendana; R. Aditama; Gerry Sastro (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aims to determine the effect of Internal Audit (X1), Employee Performance (X2) on Internal Control (Y) with the variable Intervening Fraud Prevention (Z) at PT. TransSpace Committee. This research includes causal associative research using a quantitative approach. The sample used in this study amounted to 50 employees of PT. TransSpace Committee. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is path analysis. The results of this study are that the contribution of internal audit (X1) to Internal Control (Y) is 0.311, this indicates that the contribution or influence of X1 on Y is 31.1% while the remaining 68.9% is a contribution from the variables other variables not included in the study, and also the contribution of employee performance (X2) to Internal Control (Y) is 0.173, this indicates that the contribution or influence of X2 on Y is 17.3% while the remaining 82.7% is the contribution of other variables not included in the study, and also the magnitude of the contribution of internal audit (X1) to Fraud Prevention (Z) which is equal to 0.307, this indicates that the contribution or influence of X1 on Z is equal to 30.7% while the remaining 69.3% is the contribution of other variables not included in the study, and also the size of the audience's contribution internal t (X1) and internal control (Y) on fraud prevention (Z) which is equal to 0.539, this shows that the contribution or influence of X1 & Y on Z is 53.9% while the remaining 46.1% is a contribution from the variable -Other variables not included in the study, and also the contribution of employee performance (X2) to fraud prevention (Z) is 0.177, this indicates that the contribution or influence of X2 on Z is 17.7% while the remaining is 72.3 % is the contribution of other variables not included in the study, and also the contribution of employee performance (X2) and internal control (Y) to fraud prevention (Z) which is equal to 0.522, this shows that the contribution or influence of X2 & Y to Z is 52.2% while the remaining 47.8% is contributed by other variables not included in the study, and also the amount of k the contribution of internal control (Y) to fraud prevention (Z) is equal to 0.502, this indicates that the contribution or influence of Y on Z is 50.2% while the remaining 49.8% is a contribution from other variables not included in study